Eradicating Terrorism in Asymmetric Conflict: The Role and Essence of Military Deterrence - Ünal, Mustafa Coşar (Terrorism and political violence, 2022)
This study quantitatively and qualitatively analyzes the impact and effectiveness of Turkey’s deterrence-oriented incapacitation effort throughout Turkey’s PKK conflict (1984–2018). By employing vector autoregressive (VAR) analysis, this study quantitatively finds that incapacitation did not reduce PKK violence over the long term and yielded a short-term counterproductive effect. Descriptive analysis asserts that while incapacitation had important mid-term deterring effects, it did not have any sustainable mitigation on the PKK insurrection. This is because, as this study argues, these deterrent impacts were not strategically converted into political gains/results. Considering the latest phase of the conflict, in which Turkey’s intra-state strife has become increasingly regionalized and lately internationalized in military and political terms with the emergence of the Syrian civil war, particularly the rise of the People’s Protection Units (YPG), this study claims that the sole application of an incapacitation-oriented eliminationist approach has become less relevant and less effective. The study suggests that deterrence should be considered within the strategic tit-for-tat game to force/compel the non-state actor to make the conflict more manageable by transforming it in a strategic way, in which strategy of deterrence is to be attached to visionary, long-term, and viable grand strategic political end-states and to be considered within the grand bargaining game.